2020
DOI: 10.1182/blood-2020-136427
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rituximab on the Clinical Outcomes of Primary Central Nervous System Lymphoma (PCNSL) When Added to Combination Chemotherapy: A Comprehensive Meta-Analysis

Abstract: Introduction: PCNSL is a rare diffuse large B-cell lymphoma (DLBCL) confined to the central nervous system accounting for approximately 2-5% of all primary brain tumors. Although there is no standard combination of chemotherapy, high-dose methotrexate is considered the backbone of all PCNSL chemotherapy regimens. Rituximab, an anti-CD20 antibody, has been a standard component of non-CNS DLBCL combinations since it improves progression-free (PFS) and overall survival (OS). However, the role of Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We only observed a trend in favor of rituximab, PFS at 1 years was 58% and 65% ( P = 0.18) and median OS was 56.7 months and not reached ( P = 0·74) for R-MBVP and MBVP respectively [53]. Subsequently, a meta-analysis, including 467 patients from four studies, confirmed the interest of rituximab: by showing a beneficial association with PFS (HR 0.67) and OS (HR 0.75) [54]. However, elderly patients are poorly represented and therefore the data concerning this population are insufficient to accurately determine the benefit/risk balance.…”
Section: How To Treat Newly-diagnosed Elderly Patients With Primary C...mentioning
confidence: 84%
“…We only observed a trend in favor of rituximab, PFS at 1 years was 58% and 65% ( P = 0.18) and median OS was 56.7 months and not reached ( P = 0·74) for R-MBVP and MBVP respectively [53]. Subsequently, a meta-analysis, including 467 patients from four studies, confirmed the interest of rituximab: by showing a beneficial association with PFS (HR 0.67) and OS (HR 0.75) [54]. However, elderly patients are poorly represented and therefore the data concerning this population are insufficient to accurately determine the benefit/risk balance.…”
Section: How To Treat Newly-diagnosed Elderly Patients With Primary C...mentioning
confidence: 84%